Cover Picture: Back‐Illuminated Si‐Based Photoanode with Nickel Cobalt Oxide Catalytic Protection Layer (ChemElectroChem 10/2016). Issue 10 (26th September 2016) - Bae, Dowon; Mei, Bastian; Frydendal, Rasmus; Pedersen, Thomas; Seger, Brian; Hansen, Ole; Vesborg, Peter C. K.; Chorkendorff, Ib
Abstract : The Front Cover picture shows a back‐illuminated c‐Si‐based photoanode protected by a co‐sputtered NiCoOX film, which exhibits a time‐dependent improvement in the water oxidation reaction by incorporating iron impurities from KOH electrolyte. More information can be found in the Full Paper by I. Chorkendorff and co‐workers onpage 1546 in Issue 10, 2016 (DOI:10.1002/celc.201500554 ).